Estimating ecological carrying capacity for stock enhancement in marine ranching ecosystems of Northern China - Wang, Zhaoguo; Feng, Jie; Lozano-Montes, Hector M.; Loneragan, Neil R.; Zhang, Xiumei; Tian, Tao; Wu, Zhongxin (Frontiers in Marine Science, 2022)
Marine ranching has been proposed as a promising solution to manage the depleted coastal fishery ecosystem in recent decades across China. Marine ranching integrates the practices of artificial habitat-based with aquaculture-based enhancement. Assessing the ecological carrying capacity of target species for enhancement is a precondition for determining the optimal numbers for release, particularly for those species whose habitat restrictions have been eliminated through the construction of artificial habitats in the marine ranch. A responsible approach to stock enhancement aims not only to increase total yield and stock abundance but also to consider any potential effects on ecosystem structure and function. A time-dynamic, ecosystem model was constructed using Ecopath with Ecosim for the Laizhou Bay (Bohai Sea) marine ranching ecosystem in the nearshore waters of northern China. Two sedentary target species with potential for stock enhancement, i.e., the carnivorous red snail Rapana venosa and the detritivorous sea cucumber Apostichopus japonicus, were selected to simulate and estimate their ecological carrying capacities and project their overall effects on the ecosystem. Ecological carrying capacity was defined as the maximum standing stocks of the target species that would not cause “unacceptable” impacts on the ecosystem function and resilience, i.e., not cause any other group’s biomass to fall below 10% of its original biomass. The ecological carrying capacities estimated for R. venosa and A. japonicus were 623.46 and 200.57 t·km−2, respectively, corresponding to 7.8 and 5.0 times higher than their current standing stocks. Simulations of R. venosa enhancement showed distinct effects of increased target species abundance on other functional groups and ecosystem properties. An increase in red snail biomass caused negative impacts on the biomass of most other functional groups and ecosystem indicators, such as Finn’s cycling index, transfer efficiency, and Kempton’s Q index. In contrast, the simulated A. japonicus enhancement had relatively few impacts, and the biomasses of most other functional groups and ecosystem indicators did not change or changed very slightly (<5%). The current model framework provides a means of estimating the ecological carrying capacity in commercial-scale stock enhancement practices and avoiding potential ecological risks for marine ranching in northern China.